Life expectancy in the Emilia-Romagna region: an analysis of social and geographical variability. (30th September 2020) - Di Girolamo, C; Rosaia, E M; Miglio, R; Bartolini, L; Caranci, N
Abstract: Italy and the Emilia-Romagna region record among the highest life expectancy worldwide. However, differences among geographical areas, social strata and genders have been reported at regional level. The aim of this work is to measure both geographic (among provinces) and social (among education levels) inequalities in life expectancy and to evaluate the association between education and cause-specific mortality, in the Emilia-Romagna region during the period 2012-2016. The data source is an integrated dataset based on the linkage at individual level of the regional health population register, the mortality register, and the 2011 census; this system of microdata, which is the base of the Emilia-Romagna Longitudinal Study, allows a precise calculation of the person-time at risk. The study population consisted of all individuals who were residents in the Emilia-Romagna region at the 1/1/2012 and took part to the 2011 census. Life expectancy was estimated through mortality tables reconstructed with a mixed cohort-period approach and combined with the Kannisto's method. Inequalities in mortality were estimated using a longitudinal approach and Poisson models. Educational disparities were evident even in the Emilia-Romagna region in the early 2010s; life expectancy was shorter among low-educated subjects and the gap varied: 3 years among men and approximately 1.5 years among women. Life expectancy varied also among provinces, although the gaps were smaller and men and women were closer, and there was an indication of an interaction between education and geographical areas. The risk of dying revealed social pattern and disparities were greater for respiratory diseases and for some cancers, particularly among men. This study is the first attempt to describe, through the Emilia-Romagna Longitudinal Study, educational and geographical disparities in life expectancy in the region and to suggest entry points for actions to tackle these differences. Key messages: Geographical and social inequalities in life expectancy have been reported at regional level. Those inequalities and the mortality relative risks within Emilia-Romagna during 2012-2016 were estimated. The estimates by the Emilia-Romagna Longitudinal Study highlighted disparities in life expectancy in the Emilia-Romagna region and suggest entry points for actions to tackle these differences.